Satisfactory immune response following anaphylaxis to PCECV facilitated by the use of steroids and antihistamines - Abishek Tumma; Kari Jarvinen; Brad McCall; Richard Wong; Marjoree Sehu (Taylor & Francis Group, 2020)
Introduction Rabies is fatal and can cause almost certain mortality in animals and humans. Effective post-exposure prophylaxis (PEP) using the rabies vaccine remains the cornerstone for preventing disease in humans. We present the first reported case of supporting the live purified-chick-embryo-cell rabies vaccine(PCECV) administration with prophylactic high-dose corticosteroids. Case A 39-year-old female was at high-risk of developing rabies-like disease following a bat bite. She was commenced on PEP using PCECV. Our patient developed an anaphylactic reaction with bronchospasm and a rash following her 2nd PCECV dose. Consequently, she received 2 days of loratadine and high-dose prednisolone prior to her final vaccination. During this administration in the emergency department, our patient completed the final PCECV dose. At a two-week follow-up, our patient had no evidence of rabies and had adequate viral neutralizing antibody levels detectable on serology. Discussion Type 1 hypersensitivity reactions to PCECV are rare. Only 20 anaphylactic cases have been reported from a total of 1.1million administered doses over 8 years. Individuals at higher risk of anaphylaxis include those with a prior history of allergy to either egg white, gelatin, milk, penicillin, bee venom, or beef products. Administering high dose prophylactic corticosteroids prior to vaccination can potentially induce immune tolerance and minimize subsequent risks of hypersensitivity reactions. However, data relating to its use is extremely limited to only animal and limited human case-report data from other vaccines. Conclusion We propose an alternative option which will require further research to manage vaccine-related anaphylaxis where immunization is an essential prophylactic requirement with the support of an immunologist and careful monitoring in an appropriate environment.